Skill acquisition in a professional and non-professional U16 football team: the use of playing form versus training form - Fuhre, J.; Sæther, S. A. (Journal of Physical Education and Sport, 2020)
Practice makes perfect` is a traditional statement, and practice hours, including training background, are used as an explanatory factor for success. Studies however show that hours of practice alone, are a poor predictor of future success. The content of practice sessions has been less studied, even though it naturally should be considered just as important as the amount of time spent practising. The traditional soccer practice is the more linear approach to learning, where technique and other skills are to be practised and mastered before the players are considered ready to play the game itself. The research into the field of skill development in soccer, and sports in general, is relatively coherent across different theoretical viewpoints when it comes to recommendations regarding effective practice activities. Few studies have categorize the content of practice until the concepts of training form (TF) and playing form (PF) was introduced a decade ago. The aim of this study was to compare two U16 teams, one in a professional club and one in a non-professional club, in terms of both PF and TF, including their sub-categories.We used systematic observations of soccer practice sessions to examine the type of practice activities being used. Two Norwegian U16 teams participated. Participants were systematically observed using a simple hand notation system, to provide detailed analysis of the practice activity. We evaluated these findings based on what contemporary research suggest as best to facilitate skill acquisition and development. Findings indicate that both teams use more time in Playing form activities, deemed more relevant to match performance in soccer, than training form activities who is deemed less relevant. Findings are discussed in the light of research connected to skill development, perceptual-cognitive development and expert performance. The practicalimplications of this study suggest that the practice activities in which coaches engage their players should create as many situations as possible where the players must make decisions and appropriate technical choices, and by that develop their perceptual-cognitive and technical skills. To do this, coaches should seek to use a high amount of PF in their daily coaching sessions and at the same time closely monitor the total mental and physical practice load of the players.